2016
DOI: 10.1007/s40291-016-0198-z
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacogenetic Study of Psoriasis Risk Variants in a Greek Population and Prediction of Responses to Anti-TNF-α and Anti-IL-12/23 Agents

Abstract: This study is the first in the field of pharmacogenetics in Greek psoriasis patients. Further, larger studies are required to validate our findings and replicate them in various populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 14 publications
0
54
0
2
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41][42][43] For all significant associations, except TLR9 (rs352139) and LY96 (rs11465996), similar tendencies were observed for ORs for each of the anti-TNF agents (data available on request). To our knowledge, this is one of the largest cohorts for evaluation of response in patients treated with ustekinumab 44,45 and the second largest for evaluation of anti-TNF; only a Canadian study (also involving treatment primarily for psoriatic arthritis) had more patients.…”
Section: Study Populationmentioning
confidence: 62%
“…[33][34][35][36][37][38][39][40][41][42][43] For all significant associations, except TLR9 (rs352139) and LY96 (rs11465996), similar tendencies were observed for ORs for each of the anti-TNF agents (data available on request). To our knowledge, this is one of the largest cohorts for evaluation of response in patients treated with ustekinumab 44,45 and the second largest for evaluation of anti-TNF; only a Canadian study (also involving treatment primarily for psoriatic arthritis) had more patients.…”
Section: Study Populationmentioning
confidence: 62%
“…Prowadzone są także badania, które mają udowodnić, że odpowiedź na leczenie może mieć podło-że genetyczne [36][37][38][39][40]. Jest ono związane z polimorfizmami genu TNF, receptora TNF-1B (TNFR1B) oraz genu TNFAIB3, jak również z polimorfizmami innych genów.…”
Section: Discussionunclassified
“…Studies are also conducted in order to verify whether response to treatment may be genetically conditioned [36][37][38][39][40]. It is associated with polymorphisms of the TNF gene, TNF receptor 1B (TNFR1B) and TNFAIB3 gene, as well as polymorphisms of other genes.…”
Section: Wnioskimentioning
confidence: 99%
“…Patients with HLA-C * 05 were linked to achieving PASI 75 response when treated with etanercept [29]. HLA-C SNP rs10484554 was associated with good response to anti-TNF alpha agents, especially adalimumab [39]. And lastly, HLA-DRB1 encoding SE alleles * 0101 and * 0404 were both associated with good response to etanercept [29].…”
Section: Hla Related Findingsmentioning
confidence: 97%
“…However, a few studies found associations with different HLA-C genes. HLA-C SNP rs10484554 was associated with good response to anti-TNF therapy but not with ustekinumab [39]. This study looked at the use of biologics and response for 6 months of therapy, and genotype frequency was analyzed after.…”
Section: Il-12 and Il-23 Antagonistsmentioning
confidence: 99%